2021
DOI: 10.3390/jcm10112258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Radiographical Outcomes and Complications after a Brand-New Total Ankle Replacement Design through an Anterior Approach: A Retrospective at a Short-Term Follow Up

Abstract: Recently, the progress in techniques and in projecting new prosthetic designs has allowed increasing indications for total ankle replacement (TAR) as treatment for ankle osteoarthritis. This retrospective work comprehended 39 subjects aged between 47 and 79 years old. The patients, observed for at least 12 months (mean follow up of 18.2 ± 4.1 months), have been evaluated according to clinical and radiological parameters, both pre- and post-operatively. The AOFAS and VAS score significantly improved, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Other authors showed an even greater mean sagittal ROM, with values exceeding 40 • [41][42][43]. The same authors of this paper, in 2021, reported mean values of the range of motion on the sagittal plane higher than 40 • for the same prosthetic model used in this study [14]. These studies are characterized, like many others, by a clinical, macroscopic assessment of the ROM of the ankle, performed by goniometric measurements, with mechanized devices or dynamometers, which often make them operator-dependent and poorly defined.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Other authors showed an even greater mean sagittal ROM, with values exceeding 40 • [41][42][43]. The same authors of this paper, in 2021, reported mean values of the range of motion on the sagittal plane higher than 40 • for the same prosthetic model used in this study [14]. These studies are characterized, like many others, by a clinical, macroscopic assessment of the ROM of the ankle, performed by goniometric measurements, with mechanized devices or dynamometers, which often make them operator-dependent and poorly defined.…”
Section: Discussionsupporting
confidence: 57%
“…Once the position and the size of prosthetic components are defined, the final components can be implanted with a press fit fixation. As the last step, the trial mobile insert is positioned, and the proper size is chosen considering the ligamentous balance [14].…”
Section: Surgical Instrumentation and Techniquementioning
confidence: 99%
“…This study examined patients who underwent ankle TAA surgery via the implant of the Exactech Vantage ® prosthetic model (Gainesville, FL, USA), with a mobile-bearing and anterior approach [11,19].…”
Section: Surgical Procedures and Post-operative Protocolmentioning
confidence: 99%
“…Unlike other lower limb joints, ankle OA is rarely primary; the most common etiology is a previous trauma, and this implies that the patients suffering from this degenerative arthropathy are younger than the ones affected by knee or hip OA [9]. To restore pain-free ankle mobility, Total Ankle Replacement (TAR) is among the most common elective surgical procedures performed nowadays if the conservative treatment does not improve the symptoms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The posttraumatic etiology is the most common etiology of the end-stage ankle osteoarthritis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. After failure of nonoperative treatments for severe ankle arthritis [ 5 ] including bracing/immobilization, anti-inflammatories, shoe wear and activity modification, and corticosteroid injections, patients have two operative options—arthroplasty [ 8 , 9 , 10 , 11 , 12 ] and arthrodesis [ 13 , 14 , 15 , 16 , 17 , 18 ]. Tibiotalar arthrodesis still remains the current gold standard [ 19 ].…”
Section: Introductionmentioning
confidence: 99%